2016
DOI: 10.1134/s0022093016020058
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of sleep–wake cycle development in vertebrates (Modern state of the I.G. Karmanova’s sleep evolution theory)

Abstract: The genetic basis of rest-activity circadian alternation in animal behavior is considered in the evolutionary range from bacteria to mammals. We scrutinize various concepts of sleep development in the animal world evolution as well as the I.G. Karmanova's theory of the sleepwake cycle evolution in vertebrates, beginning from wakefulness-primary sleep (or protosleep) in fish and amphibians through wakefulness-intermediate sleep in reptiles to wakefulness-slow wave sleep (SWS) and paradoxical sleep (PS) in birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Overall sleep duration is inversely related to the overall activity duration. We calculated sleep duration in the main groups of endotherms from the data in the work of Campbell and Tobler (1984) , with the addition of some later sources for monotremes and palaeognaths ( McNamara et al 2009 ; Aristakesyan 2016 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall sleep duration is inversely related to the overall activity duration. We calculated sleep duration in the main groups of endotherms from the data in the work of Campbell and Tobler (1984) , with the addition of some later sources for monotremes and palaeognaths ( McNamara et al 2009 ; Aristakesyan 2016 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In endothermic vertebrates, specifically birds and mammals (and only in these two groups), two distinct modes of sleep are alternated: rapid eye movement sleep ( REM , or fast-wave [ FWS ] sleep) and non- REM sleep (or slow-wave sleep [ SWS ]) ( Capellini et al 2008 ). Overall, the duration of sleep and non- REM sleep is directly related to the intensity of metabolism, body mass and brain size ( Aristakesyan 2016 ). It has been shown that, within vertebrates, the duration of sleep decreases from fishes and amphibians to birds and mammals ( Karmanova 1982 ).…”
Section: Introductionmentioning
confidence: 99%
“…The apparent ubiquitousness of sleep across taxa makes the study of the evolution of sleep hugely compelling ( Anafi et al, 2019 ; Aristakesyan, 2016 ). Sleep is responsive to both internal and external conditions, meaning that across phylogeny there is great variation in sleep architecture, timing and behaviour ( Ungurean et al, 2020 ).…”
Section: Evolution Of Sleepmentioning
confidence: 99%
“…Regarding the remainder, one was eclectic, simply demanding for non-homeothermic animals the same rigorous methods used for ascertaining sleep in mammals and, vice-versa, applying to mammals the molecular techniques developed in invertebrates (Hartse, 2017). The last one (Aristakesyan, 2016) only referred the vertebrate sleep, recognizing therefore the existence of primitive behavioral sleep in poikilothermic vertebrates and assuming therefore the evolutionary continuity of sleep in the vertebrate phylum. Hopefully, the present review will shed light first, on the monophyletic or polyphyletic nature of animal sleep and second, on explaining that sleep appeared in mammals because of an evolutionary bottleneck that forced, in their reptilian ancestors, a change in chronotype, from diurnal, to nocturnal.…”
Section: Introductionmentioning
confidence: 99%